Spirituality and Personhood: Homo Liturgicus and Pagkatao in Conversation - Samdao, Francis Jr. S. (Asia journal of theology, 2023)
This essay places James K. A. Smith’s homo liturgicus (liturgical human) in conversation with the Filipino concept of pagkatao (personhood). For Smith, humans are desiring creatures, and they are formed through practices, daily routines, cultural texts, and the liturgical sites where they spend their time. Smith’s proposals within his homo liturgicus are not alien to the Filipino worldview. Filipinos see a person holistically and view reality as dynamic, which manifests in the pagkataong Pilipino (Filipino personhood), particularly the loob (the core of personhood) and kapwa (the shared self). Furthermore, the formation of a human being is not only through the ideas that enter the mind but also via cultural texts (songs, comics, movies, drama, proverbs, stories, and others). I argue that homo liturgicus and pagkatao reject Cartesian thought, specifically the naturalistic view of reality, the overemphasis on cognition, and extreme individualism. I then propose a Filipino Christian spirituality that is post-cognitive, post-individual, and post-dualist.